(untitled) (Iranian Journal of Kidney Diseases, 2011)
Resistant hypertension is an increasingly common medical problem, and patients with this condition are at a high risk of cardiovascular events. The prevalence of resistant hypertension is unknown, but data from clinical trials suggest that 20% to 30% of hypertensive individuals may be resistant to antihypertensive treatment. The evaluation of these patients is focused on identifying true resistant hypertension and contributing and secondary causes of hypertension, including hyperaldosteronism, obstructive sleep apnea, chronic kidney disease, renal artery stenosis, and pheochromocytoma. Treatment includes removal of contributing factors, appropriate management of secondary causes, and use of effective multidrug regimens. More established approaches, such as low dietary salt and mineralocorticoid receptor blockers, and new technologies, such as carotid stimulation and renal denervation, have been used in the management of patients with resistant hypertension.